Extraction of Geological Structural Lineaments in Northern Kuwait Using High Resolution Landsat 8 ETM+ Satellite Images and Edge Enhancement Techniques - Al-Azemi, Ahmad Mohammad; RaoDivi, Prof. RaoDivi (Journal of engineering sciences and information technology, 2017)
Earth consists of hard rock layers where water is restricted to secondary permeability, and thus to fractures and the weather zones. Satellite images, aerial photographs and digital elevation models will give lineament information. Recent advances in digital image processing allow such lineament extraction to be accomplished in semi-automatic to fully automatic approaches. Precise delineation and mapping of geological structural lineaments is very much needed in Northern Kuwait in view of their close spatial association with subsurface tectonic fractures in oil fields at deep levels and groundwater fields (aquifers) at shallow depths. As such, high spatial resolution remote sensing multispectral image data (Landsat 8 ETM+ satellite) will be used delineate and map the lineaments. Lineaments are linear features which provide information about the underlying geological structure. Their analysis are widely considered in the location or sitting of suitable groundwater exploration sites since the water will tend to flow along the fracture zones. The major objective was to extract the lineaments in Northern Kuwait, with a view of using the analysis for groundwater exploration in the future to mitigate the requirement of groundwater in the area. The analysis was carried out using Band 5, 6 and 7 of Landsat 8 (OLI), which was processed using the edge enhancement filters available to extract the lineaments in the study area. These were then verified using manually digitized lineaments from a geological map partly covering the region and false color composites of the study area. The results showed that the semi-automatic extraction of lineaments can yield tangible results using optical imagery. However, the lineaments still require verification through comparison with known lineaments. Filters which are Sobel, Laplacian and Directional filtering of Band 5, 6 and 7 of Landsat 8 proved to be useful in visual identification and verification of lineaments.